2021
DOI: 10.3390/su13158446
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Quality in Naturally Ventilated Classrooms. Lessons Learned from a Case Study in a COVID-19 Scenario

Abstract: This paper describes the implementation of a series of ventilation strategies in a nursery and primary school from September 2020, when the government decided to resume the students’ face-to-face activity in the middle of a COVID scenario. Air quality and hygrothermal comfort conditions were analysed before the pandemic and compared for different ventilation configurations in a post-COVID scenario. Ventilation strategies included the protocols issued by the Public Administration, while others were developed ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 18 publications
1
25
0
2
Order By: Relevance
“…In their study, their results showed a 30% improvement in the daily average CO2 concentration compared to the values measured before the COVID-19 disease. In addition, the research conducted by Meiss et al [47] on natural ventilation strategies in classrooms concluded that continuous natural cross-ventilation ensured the lowest CO2 levels compared to the other scenarios studied. Therefore, cross-ventilation with opening windows and doors is recommended for health emergency situations.…”
Section: And 60%mentioning
confidence: 96%
“…In their study, their results showed a 30% improvement in the daily average CO2 concentration compared to the values measured before the COVID-19 disease. In addition, the research conducted by Meiss et al [47] on natural ventilation strategies in classrooms concluded that continuous natural cross-ventilation ensured the lowest CO2 levels compared to the other scenarios studied. Therefore, cross-ventilation with opening windows and doors is recommended for health emergency situations.…”
Section: And 60%mentioning
confidence: 96%
“…For example, air quality can be reduced due to higher levels of pollutants from wildfires and other activities, which have shown to lead to strong impacts upon contracting COVID-19 ( Liu et al, 2020a ; Meo et al, 2020 ; Middleton, 2020 ; Curtis, 2021 ; Dragone et al, 2021 ; Kiser et al, 2021 ; Leifer et al, 2021 ; Setti et al, 2020 b; Zhou et al, 2021 a). Furthermore, natural ventilation for optimal indoor air quality is not sufficient to control the potential spread of SARS-CoV-2 ( Li et al, 2004 ; Meiss et al, 2021a ; WHO, 2021a). The host of SARS-CoV-2 may contribute to its spread ( De Wit and Ricketts, 2021 ) through means of water from agriculture ( Coronado et al, 2021 ) or organic human waste ( De Wit and Ricketts, 2021 ), which may affect marine ecosystems ( Guo et al, 2021 ; Mathavarajah et al 2021 ) and individuals through buildings ( Wang et al, 2021 ).…”
Section: Impact Of Ambient Environments On Sars-cov-2mentioning
confidence: 99%
“… Lee (2020) estimated a particle size of 4.7 μm carrying SARS-CoV-2. Indoor NO 2 , PM 1 , PM 2.5 and PM 10 may indicate potential presence, but do not directly represent SARS-CoV-2 ( Bianconi et al, 2020 ; Li et al, 2020a ; Baboli et al, 2021 ; Bazzazpour et al 2021 ; Li et al, 2021a Meiss et al, 2021a ; Nor et al, 2021 ). Similarly to SARS-CoV, approximate temperatures of 20°C - 28°C and relative humidity of 20% - 80% are reported to be optimal conditions for the presence of SARS-CoV-2, but do not directly lead to its transmission ( Casanova et al, 2010 ; Spena et al, 2020 ; Baboli et al 2021 ; Raines et al, 2021 ; Razzini et al 2021).…”
Section: Indoor Airmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, COVID-19 pandemic has prompted renewed interest in the assessment of deficient indoor air quality conditions, especially in educational buildings. Notably, recent studies point to the need for indoor air quality monitoring and prediction solutions based on IoT and machine learning capabilities (Mumtaz et al, 2021) as well as reassessing ventilation protocols (Alonso et al, 2021;Meiss et al, 2021). Accordingly, we further discuss the insight gathered from the data collected during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 95%